Two‐Step Autohydrolysis Pretreatment: Towards High Selective Full Fractionation of Wheat Straw. Issue 11 (1st September 2020) - Conrad, Marc; Smirnova, Irina
Abstract: Pretreatment is necessary to increase the enzymatic digestibility of lignocellulosic biomass. Here, degradation reactions of solubilized pentoses to furfural and others are undesired regarding the reduced product yield and increasing downstream processing efforts. In this work, the use of the unit operation configuration was successfully shown to reduce degradation reactions. In the used two‐step autohydrolysis pretreatment, the reaction is stopped before degradation takes place. The pentoses are removed by water leaching to make them unavailable for degradation in a second autohydrolysis treatment. The overall sugars yield is increased, and the furfural formation is decreasing while maintaining the high lignin purity using the two‐step autohydrolysis pretreatment. Abstract : For an economically feasible biorefinery the biomass substrate must be fully fractionated with high yield, selectivity and concentrations. The two‐step autohydrolysis pretreatment of wheat straw is an interesting approach to do so using only water, enzymes and high temperature. This work provides an experimental proof of principle.